CURRENT LEARNING MEDIA: USING AUGMENTED REALITY (AR) AS AN ALTERNATIVE DIGITAL LEARNING MEDIA - Rahmawati; Maliatul Fitriyasari; M. Rifqi Atsani (Adisam Publisher, 2025)
Augmented Reality (AR) technology has developed rapidly and become one of the significant innovations in the world of modern education. AR offers an interactive learning experience that combines digital elements, such as 3D objects and animations, into the real world, thereby increasing student engagement and motivation. This study aims to explore the potential use of AR as an alternative digital learning media in various subjects and levels of education. This study shows that AR can help students understand abstract concepts, visualize learning materials in a more concrete way, and support project-based learning. In addition, AR also allows flexible and accessible learning, especially through mobile devices that are widely used by students. However, the implementation of AR in education still faces challenges, such as limited technological infrastructure, lack of teacher competence, high development costs, and difficulties in measuring learning effectiveness. To overcome these challenges, support is needed from various parties, including the government, educational institutions, and technology developers. With effective collaboration, AR has the potential to become an innovative and effective learning media in preparing students to face challenges in the digital era.